Using eportfolios to encourage responsible feedback - Lucia Morales; Amparo Soler Dominguez (Laureate Education Inc, 2015)
This article aims to look at the value that ePortfolios can add to business studies, specifically in the financial field. In order to answer the question, Do ePortfolios contribute to the development and enhancement of responsible feedback in the classroom?, the study analyzed the work done by postgraduate students pursuing a Master's degree in finance. A total of 151 ePortfolios were reviewed and analyzed, and a selection of comments from students is presented in order to support the main findings of the literature review. The authors considered this approach to be appropriate in order to offer an objective analysis on existing research and how their own students' views blend with developed literature in the area. The authors also offer their own know-how on how ePortfolios can be integrated as part of the postgraduate learning experience. The researchers identified ePortfolios as being a complementary tool that help educators and students to get a better understanding of the course material and offer students an opportunity to reflect on their own learning and course performance. They also identified a lack of research on how ePortfolios can be used as part of the students learning experience in postgraduate education specialised in finance. DOI: 10.18870/hlrc.v5i3.245